Immobilization for carbon ion beam ablation of cardiac structures in a porcine model - Prall, Matthias; Lugenbiel, Patrick; Thomas, Dierk (Physica medica, 2017)
Introduction: Whereas hadron therapy of static targets is clinically established, treatment of moving organs remains a challenge. One strategy is to minimize motion of surrounding tissue mechanically and to mitigate residual motion with an appropriate irradiation technique. In this technical note, we present and characterize such an immobilization technique for a novel noncancerous application: the irradiation of small targets in hearts with scanned carbon ion beams in a porcine model for elimination of arrhythmias. Material and methods: A device for immobilization was custom-built. Both for the treatment planning 4D-CT scan and for irradiation, breath-hold at end-exhale was enforced using a remotely-controlled respirator. Target motion was thus reduced to heartbeat only. Positioning was verified by orthogonal X-rays followed by couch shift if necessary. Reproducibility of bony anatomy, diaphragm, and heart position after repositioning and between repeated breath-hold maneuvers was evaluated on X-rays and cardiac-gated 4D-CTs. Treatment was post hoc simulated on sequential 4D-CTs for a subset of animals, after immediate repositioning and after a delay of one week, similar to the delay between imaging and irradiation. Results: Breath-hold without repositioning was highly reproducible with an RMS deviation of at most one millimeter. 4D-CTs showed larger deformations in soft tissue, but treatment simulation on sequential images resulted in full target coverage (V95 >95%). Conclusion: The method of immobilization permitted reproducible positioning of mobile, thoracic targets for range-sensitive particle therapy. The presented immobilization strategy could be a reasonable approach for future animal investigations with the ultimate goal of translation to therapy in men.